RELEVANSI PENDIDIKAN DENGAN SURAH AL-‘ASHR - Desriadi, Desriadi; Hardiman, Dodon; Faraditsi, Fauzia (Al-Ashri: Ilmu-Ilmu Keislaman, 2023)
This research is motivated by the fact that the education process so far has not been fully successful in developing Indonesian people with character. In fact, some say that education has failed, because many school graduates or graduates are skilled at answering exam questions, have intelligent brains, but are mentally and morally weak. Education has an important role in instilling faith, patience, independence, discipline, responsibility, creativity and noble character. Surah Al-'Ashr contains several pillars of education which can be used as guidelines by students and educators in carrying out the daily learning process. This research is library research (library research), namely research carried out in libraries or museums on existing materials in the form of books, magazines or other documents. The primary data source for this research is the Al-Qur'an Surah Al-"Ashr, then Tafsir-Tafsir Al-Quran related to the discussion raised by the author. The relevance of Surah Al-'Ashr to education is that in this verse there are characters that students must have, including the character of faith, charity.saleh and patience. Sentence fragment "dinner in the morning" Surah Al-'Ashr explains that if a person has a religious character or has faith in himself, then he will avoid the losses described in the second verse. Students must be instilled with the character of faith from an early age, such as the character of faith contained in Q.S Al-'Ashr. Next is the character of doing good deeds. Good deeds are good works that are beneficial for oneself and others based on Islamic law and are sincere for the sake of Allah SWT alone. Many of today's students are smart in the academic aspect, but lack good morals, such as very rarely carrying out the pious deeds contained in Surah Al-'Ashr. So it is appropriate for today's students to imitate the character of doing good deeds in Surah Al-'Ashr. Then the patient character. This patient trait must be possessed by an educator. Because the task of an educator is not only to teach knowledge, whether in the form of theory or difficult numerical formulas, but also to always give advice or give advice to students about the truth and to be patient in doing so. Educators should not feel fed up or bored in giving advice to their students, educators must have extra patience in the educational process.